It does not need to be perfect! Two teacher educators’ quest to enhance online instruction with videos - Elena Andrei; Mary Frances Buckley-Marudas (Networks: An Online Journal for Teacher Research, 2019)
Two early career literacy and language teacher educators who have digital literacies at the core of their professional and scholarly pursuits share their quest to enhance their online instruction. The authors wanted to identify one new improvement for their online courses in an effort to engage the students and support a more connected learning community. The improvement was instructor-made videos. Once the first video was shared and posted, weekly peer support, the premises of “keeping it simple” and “it does not need to be perfect” seemed to be critical in the implementation of videos for the online instruction. The authors continue to use instructor-created videos in their courses as part of their routine online teaching.
Keywords: online teaching; videos; teacher educators